2008
DOI: 10.1086/590011
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of the Physical Examination and Imaging Tests for Osteomyelitis Underlying Diabetic Foot Ulcers: Meta‐Analysis

Abstract: Accurate diagnosis of osteomyelitis underlying diabetic foot ulcers is essential to optimize outcomes. We undertook a meta-analysis of the accuracy of diagnostic tests for osteomyelitis in diabetic patients with foot ulcers. Pooled sensitivity and specificity, the summary measure of accuracy (Q*), and diagnostic odds ratio were calculated. Exposed bone or probe-to-bone test had a sensitivity of 0.60 and a specificity of 0.91. Plain radiography had a sensitivity of 0.54 and a specificity of 0.68. MRI had a sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
164
0
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(174 citation statements)
references
References 35 publications
2
164
0
8
Order By: Relevance
“…Although it is accurate, leukocyte-labeling scintigraphy accompanying bone marrow scan is doomed due to inaccessibility, labor intensity, and the risk of contamination [35]. In addition, bone scan can be a sensitive method for the diagnosis of osteomyelitis.…”
Section: Resultsmentioning
confidence: 99%
“…Although it is accurate, leukocyte-labeling scintigraphy accompanying bone marrow scan is doomed due to inaccessibility, labor intensity, and the risk of contamination [35]. In addition, bone scan can be a sensitive method for the diagnosis of osteomyelitis.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, our findings overall complement those identified in a systematic review and meta-analysis of diabetic foot infections which suggests that factors increasing the likelihood of osteomyelitis are probing to bone, ulcer size >2 cm 2 , ulcer duration >2 weeks or erythrocyte sedimentation rate >70. [5][6][7][8] Some case series suggest that a negative probe to bone test has a strong negative predictive value (0.98), whereas a positive probe to bone test only has a positive predictive value of 0.57. 9 In our series, however, the inability to probe to bone did not reliably exclude osteomyelitis, consistent with many studies that suggest no single factor can reliably include/ exclude osteomyelitis.…”
Section: Discussionmentioning
confidence: 99%
“…9 In our series, however, the inability to probe to bone did not reliably exclude osteomyelitis, consistent with many studies that suggest no single factor can reliably include/ exclude osteomyelitis. [5][6][7] A limitation of this small case series review is that bone biopsy was not performed for microbiological identification. Other studies of diabetic foot infection have found that bone biopsy guided antibiotic treatment may be more effective.…”
Section: Discussionmentioning
confidence: 99%
“…Direkt grafi, Amerikan Radyoloji Koleji'nin Uygunluk Kriterleri (21) listesine göre en uygun yöntem olarak kabul görse de, osteomiyelitin tanısında düşük duyarlılık ve özgüllüğe sahip olup, tutulum direkt grafi ile iki hafta sonra görülebilmektedir (13,22). Kemik demineralizasyonu, periost reaksiyonu ve kortikal destrüksiyonu tespit edebilir; ancak, bu bulguların direkt grafide görülebilmesi için, enfeksiyonun başlangıcından sonra 14 günlük bir süre geçmesi gereklidir.…”
Section: Radyolojikdeğerlendirmeunclassified